2D Metal Oxides: Two‐Dimensional Metal Oxide Nanomaterials for Next‐Generation Rechargeable Batteries (Adv. Mater. 48/2017). Issue 48 (19th December 2017) - Mei, Jun; Liao, Ting; Kou, Liangzhi; Sun, Ziqi
Abstract : Two‐dimensional metal oxides have been the focus of intense research in recent years, offering the opportunity for their use in energy conversion and storage devices, such as lithium‐ion, sodium‐ion, lithium–sulfur, and lithium–air batteries. In article number1700176, Ziqi Sun and co‐workers review recent progress in this field, along with the current challenges and opportunities for their application toward high energy density, high power density, and cyclic stability.